Expanding the KIF4A‐associated phenotype. Issue 12 (3rd August 2021) - Kalantari, Silvia; Carlston, Colleen; Alsaleh, Norah; Abdel‐Salam, Ghada M. H.; Alkuraya, Fowzan; Kato, Mitsuhiro; Matsumoto, Naomichi; Miyatake, Satoko; Yamamoto, Tatsuya; Fares‐Taie, Lucas; Rozet, Jean‐Michel; Chassaing, Nicolas; et al.
Abstract: Kinesin super family (KIF) genes encode motor kinesins, a family of evolutionary conserved proteins, involved in intracellular trafficking of various cargoes. These proteins are critical for various physiological processes including neuron function and survival, ciliary function and ciliogenesis, and cell‐cycle progression. Recent evidence suggests that alterations in motor kinesin genes can lead to a variety of human diseases, including monogenic disorders. Neuropathies, impaired higher brain functions, structural brain abnormalities and multiple congenital anomalies (i.e., renal, urogenital, and limb anomalies) can result from pathogenic variants in many KIF genes. We expand the phenotype associated with KIF4A variants from developmental delay and intellectual disability with or without epilepsy to a congenital anomaly phenotype with hydrocephalus and various brain anomalies at the more severe end of phenotypic manifestations. Additional anomalies of the kidneys and urinary tract, congenital lymphedema, eye, and dental anomalies seem to be variably associated and overlap with clinical signs observed in other kinesinopathies. Caution still applies to missense variants, but hopefully, future work will further establish genotype–phenotype correlations in a larger number of patients and functional studies may give further insights into the complex function of KIF4A.